Gender digital divide and political participation in selected Arab countries - Raïq, Hicham; Rabah, Saddek; Al-Mannai, Abdulaziz Ali M.; Malkawi, Asma H.; Ali, Abdel-Samad M.; Tabishat, Mohammed; Al-Fahim, Fatima Abdulrahman M. S.; Al-Marri, Rafaa Hamad S. A. (Frontiers in Communication, 2025)
IntroductionThis study examines the gendered digital divide and its impact on political participation in 10 Arab countries. It focuses on how unequal internet access influences political engagement in a region characterized by some of the lowest global rates of women’s political participation.MethodologyThe study uses data from the Arab Opinion Index and applies multivariate logistic regression stratified by gender. It analyzes the digital divide with internet usage, types of social media, and users’ purposes as indicators, using age, income, education level, marital status, and employment as control variables.ResultsThe gender digital divide is less evident in countries with high internet access, while it remains more pronounced in states where internet usage is limited, particularly among women. Even if there is a weak relationship between internet use and political participation, our findings indicate that targeted use (especially when centered on public concerns) can meaningfully boost political engagement.ImplicationsThese results point to the importance of going beyond internet access alone. What also matters is how the internet is used and for what purpose. When digital tools are used to address public concerns or connect with broader communities, they become a means of influence, not only through communication, but also through political participation. In these cases, women are more likely to express their opinions, gain power, and take part in political change across the Arab world.